TINGKAT KECERDASAN SOSIAL EMOSIONAL ANAK USIA DINI DI TINJAU DARI POLA ASUH ORANG TUA - Indaria Tri Haryani; Beny Dwi Pratama; Djumaryanti Djumaryanti (JURNAL LENTERA ANAK, 2022)
Social conditions that occur in our country have children who dare to kill their own parents because they feel revenge due to being scolded by their parents, there are also rapes with underage perpetrators and many other negative incidents and events. To improve social-emotional intelligence in children, proper parenting is needed from parents. This study aims to determine the differences in children's social emotional intelligence in terms of parenting patterns. At Pujasiwi Kindergarten Surabaya, based on observations made by researchers, there was an unfavorable attitude or character from the students in group A of Pujasiwi Kindergarten. So that researchers are interested in conducting research on the emotional social intelligence of early childhood in terms of parenting patterns in TK Pujasiwi Surabaya. The research method uses qualitative, data collection techniques are obtained from tests, interviews, observations, and questionnaires, the population of this study is parents of students who live around the kindergarten.  So that researchers are interested in conducting research on the emotional social intelligence of early childhood in terms of parenting patterns in TK Pujasiwi Surabaya. The research method uses qualitative, data collection techniques are obtained from tests, interviews, observations, and questionnaires, the population of this study is parents of students who live around the kindergarten. Pujasiwi. The number of samples as many as 28 residents of RW. XIII and its surroundings  Putat Jaya Village. The result of this research is that parenting has a great impact on the emotional social intelligence of early childhood, because if parents are able to educate children with good and correct parenting patterns, they can shape the character of children with noble character.